White rust: Plant-microbe interaction and plant breeding perspective on Indian mustard: White rust: Plant-microbe interaction and plant breeding perspective on Indian mustard - D PRAKASH,; K SRIVASTAVA,; B SINHA, (Journal of Oilseeds Research, 2023)
White rust is an important disease of Indian mustard which results in appreciable yield losses. A monogenic dominant gene has been responsible for resistance against this pathogen in B. juncea. In the pathogen, avirulence has been observed to be dominant, governed by a single gene. R gene (resistance gene) present in resistant lines of B. juncea, encodes CC-NB-LRR (coiled coil nucleotide binding leucine rich repeat) protein whereas, susceptible lines have truncated LRR domain of the same protein. Resistant and moderately resistant lines have higher amount of chlorophyll, sugars and total phenols than susceptible cultivars, throughout crop growth. Increased accumulation of phytoalexins such as spirobrassinin, cyclobrassinin and rutalexin have been observed in resistant lines compared to, susceptible ones upon infection by fungi. Molecular markers tagged to R gene are being used in resistance breeding programmes. Scientists have developed intron polymorphism (IP) markers namely;At5g41560, At5g41940 and At2g36360 for positive selection of white rust resistance and, simple sequence repeat (SSR) marker, At2g34700, for negative selection of resistance in different rust resistant sources. The major issue in use of these markers is their transferability as they do not show association with R gene in different set of crosses.